Balance Study of Clothing Single-Piece Production Line Based on Dual-Population Genetic Algorithm (Journal of Fiber Bioengineering and Informatics, 2024)
Currently, line production is the mainstream production method for various clothing enterprises.Therefore, optimising and improving the production line plays a crucial role in promoting the developmentof manufacturing enterprises. To solve the problems of unbalanced operation time and low production linebalance rate of each workstation of the garment sewing production line, a multi-objective optimisationmathematical model with the minimum smoothing index and the largest production line balance ratewas established, and the dual-population genetic algorithm was designed in the MATLAB environment.The jeans (front piece) were used as an example to be simulated and verified in simulation software.Achieve load balancing at workstations, save production costs, and eliminate overproduction betweenjobs. The research results show that the smoothness index of the optimised production line has beenreduced from 20.89 to 8.43, and the production line balance rate has been increased from 77.57% to89.06%, which meets the requirements of enterprise process planning and can deliver on time. Thisverifies that the model proposed in this paper can effectively solve the production balance problem of asingle clothing production line.
Keywords: Dual-population genetic algorithm; Balance optimisation; Garment sewing line; Simfactory software.